Transfrontier Conservation in Africa At the Confl uence of Capital, Politics and Nature - Ramutsindela, Maano (CABI, 2014)
The book suggests that an adequate analysis of transfrontier conservation initiatives in Africa would have to go beyond explaining specific cases and the circumstances surrounding them if we are to achieve a comprehensive understanding of these initiatives. This is imperative, not least because TFCAs provide the platform on which various interests are pursued at, and between, various scales. The book challenges the emerging and common view of TFCAs as a southern African phenomenon or, at worst, a South African experience. Instead, it argues that TFCAs should be understood in the context of the intersections between the environmental movement and the private sector, and the place and role of the state – individually and collectively – in those intersections. It concludes that events and processes that shaped TFCAs and their emergence in Africa are not perfectly discrete, but are linked to the trajectories of environmentalism and associated practices in a changing socio-political environment.